337 Effect of the quantity of concentrate offered in an automated milking system on dry matter intake, milking frequency, milk and milk component yield, and ruminal fermentation when provided isocaloric diets. (7th December 2018) - Paddick, K; DeVries, T; Schwartzkopf-Genswein, K; Steele, M; Mutsvangwa, T; Penner, G
Abstract: The objective was to determine if the quantity of concentrate provided in an automatic milking system (AMS), under isocaloric conditions, affects DMI, voluntary attendance to the AMS, milk and milk component yields, and ruminal fermentation. Eight ruminally-cannulated primiparous cows were used in a replicated 4 - 4 Latin square design with 28-d periods. Treatments included 0.5, 2.0, 3.5, and 5.0 kg/d DM of pellet offered in the AMS, with an equivalent reduction of the same pellet in the partial mixed ration (PMR). Within each period, d 21 to 24 were used for DMI, milking performance, and ruminal pH determination, while d 25 to 28 were used for ruminal ammonia concentration and digestibility determination. Consumption of AMS pellet linearly increased (P < 0.01) equating to 0.50, 2.00, 3.49, and 4.93 kg/d (P < 0.01), with daily standard deviation of 0.06, 0.42, 0.51, and 0.85 kg/d, respectively (P < 0.01). The PMR DMI decreased linearly with increasing AMS concentrate allocation (P < 0.01), but total DMI (PMR+AMS) was not affected (25.3 kg/d, P = 0.40). Milking frequency (3.22/d, P = 0.82), milk yield (37.5 kg/d, P = 0.59), milk fat yield (1.43 kg/d, P = 0.46) and protein yield (1.22 kg/d, P = 0.42) were not affected, however milk urea nitrogen decreased linearly with increasing AMS concentrate (P = 0.02). Ruminal pH was not affected by AMS concentrate (6.18, P = 0.62). Ruminal ammonia decreased linearly (P = 0.01) with increasing AMS concentrate. Digestibility of DM (P = 0.096) and NDF (P = 0.056) tended to decrease linearly, while ether extract digestibility decreased linearly (P < 0.01) with increasing concentrate in the AMS. These data indicate that large quantities of AMS concentrate allocations do not positively affect DMI, voluntary visits to the AMS, milk and milk component yield or ruminal fermentation.